KEEFEKTIFAN PEMBELAJARAN DARING MENGGUNAKAN MEDIA ONLINE PADA MATA PELAJARAN BAHASA INDONESIA DI SMP MUHAMMADIYAH IMOGIRI - Tutut Romania; Mawar Shuci (Jurnal Komposisi, 2020)
The purpose of writing this article is to determine the effectiveness of online learning in Indonesian at SMP Muhammadiyah Imogiri. The subjects of this study were VII grade students of SMP Muhammadiyah Imogiri. The method used in this research is qualitative research using a descriptive approach and tapping techniques. Qualitative research, according to Strauss in Golafshani (2003, p. 600), is a type of research about all things whose research results do not go through statistical or counting procedures. Meanwhile, the descriptive approach in this study aims to make a systematic, factual, and accurate description of the facts and characteristics of a particular population or object to describe the reality that is happening without explaining the relationship between variables (Kriyantono, 2008, p. 67-68) . The results of the analysis of the Effectiveness of Online Learning Using Online Media in Indonesian Language Subjects at SMP Muhammadiyah Imogori can be concluded that the effectiveness of students in participating in learning and collecting assignments online or online is very good.